2009
DOI: 10.1093/jjco/hyp146
|View full text |Cite
|
Sign up to set email alerts
|

A Phase II Study of Sunitinib in Japanese Patients with Metastatic Renal Cell Carcinoma: Insights into the Treatment, Efficacy and Safety

Abstract: In Japanese patients with RCC, sunitinib is consistently effective and tolerable with similar risk/benefit as that in Western patients, though there was a trend toward greater antitumour efficacy and higher incidence of haematological adverse events in Japanese patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
86
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(98 citation statements)
references
References 21 publications
9
86
3
Order By: Relevance
“…Compared to the Caucasian population, Asian people in general have a relatively lower body surface area (BSA), and as a result drug exposure in Asian patients may be higher after a standard dose. However, no or only a relatively small effect of BSA on sunitinib pharmacokinetics was identified in both Caucasian [44] and Japanese patients [46]. In contrast, the lean body mass (LBM) has recently been identified to be related with sunitinib and SU12662 exposure in 92 patients with solid tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the Caucasian population, Asian people in general have a relatively lower body surface area (BSA), and as a result drug exposure in Asian patients may be higher after a standard dose. However, no or only a relatively small effect of BSA on sunitinib pharmacokinetics was identified in both Caucasian [44] and Japanese patients [46]. In contrast, the lean body mass (LBM) has recently been identified to be related with sunitinib and SU12662 exposure in 92 patients with solid tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Sunitinib is widely used for the treatment of advanced renal cell carcinoma and imatinib-refractory gastrointestinal stromal tumors, and was recently approved for pancreatic neuroendocrine tumors by the U. S. Food and Drug Administration and European Medicines Agency. Several clinical trials have demonstrated that sunitinib significantly improves overall survival as well as progression-free survival in patients with advanced renal cell carcinoma (Motzer et al, 2007(Motzer et al, , 2009) and imatinib-refractory gastrointestinal stromal tumors (Demetri et al, 2006); however, patients taking sunitinib are often forced to reduce the dose or discontinue treatment because of frequent adverse events, such as thrombocytopenia, liver dysfunction, and hand-foot syndrome (Demetri et al, 2006;Motzer et al, 2007Motzer et al, , 2009Hong et al, 2009;Uemura et al, 2010;Yoo et al, 2010). In addition, tumor regrowth observed during drug-off periods is recognized as a serious problem (Chow and Eckhardt, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Hypothyroidism was also considered to be an important AE associated with sunitinib treatment, for which 31 patients (53.4%) required medication during this study. ficacy and safety of these agents in the Western world [7,8,11], only few reports have described findings in Asian populations [12][13][14]19]. In 2010, Tomita et al reported updated results from a Phase II trial of sunitinib in the Japanese population [14].…”
Section: Evaluation Of Aesmentioning
confidence: 99%
“…In addition, only patients with clear-cell histology were eligible for the study [8]. Although sunitinib has been universally prescribed to patients with mRCC, few studies have examined the efficacy and safety of this agent in daily clinical practice, especially in patients of Asian ethnicity [12][13][14][15]. Here, we assessed the efficacy and safety of sunitinib in Japanese patients with mRCC in general clinical practice.…”
Section: Introductionmentioning
confidence: 99%